Entomacrodus solus, a new species of blenny (Perciformes, Blenniidae) from the Red Sea - Williams, Jeffrey T.; Bogorodsky, Sergey V. (Zootaxa, 2010)
Entomacrodus solus, new species, is described on the basis of 35 specimens collected by J.E. Randall on a shallow rocky shore at the end of a mangrove channel at Ras Mohammed, Red Sea. The new species belongs to the Nigricans Species Group, which is distinguished from all other blennies in having about the medial third of the ventral margin of the upper lip entire and the lateral thirds crenulate. Within the group, now consisting of 11 species, the new species is distinguished by having only single pores at each preopercular pore position, typically three predorsal commissural pores, and small white spots on lips, head and body. Entomacrodus solus is the only species of the circumtropical genus Entomacrodus known from the Red Sea.